PELATIHAN STEAM UNTUK MEMBANGUN KREATIVITAS DAN INOVASI ANAK SD DI SDN 1 PERAMPUAN KABUPATEN LOMBOK BARAT: STEAM - Nurfitriah; Fithri, Nurshahifah; Naola Salsabila; Ibrahim (Jurusan Ilmu Pendidikan, FKIP, Universitas Mataram, 2024)
STEAM (Science, Technology, Engineering, Arts and Mathematics) training at SDN 1 Perampuan, West Lombok, aims to improve the creativity, innovation and critical thinking skills of grade 4 students. Through an interactive and practical approach, this training involves students in experiments simple and collaborative projects, allowing them to integrate various disciplines. This activity will be carried out in September 2024 using observation, experimentation, collaborative projects and feedback-based evaluation methods. Initial observations are carried out to identify learning needs and challenges, followed by preparation of materials and tools. The training involved an introduction to basic STEAM concepts, simple experiments such as building a mini volcano, technology development through basic coding, and the integration of art and mathematics in bridge design. Each session features a collaborative project, where students work in groups to apply the knowledge they have gained. Evaluation is carried out through project presentations and providing feedback to improve and enhance student skills. The results of the training showed high student enthusiasm, as well as increased understanding of basic STEAM concepts. Final project evaluations provide constructive feedback, encouraging students to continue learning and applying STEAM concepts in everyday life. With the support of the STEAM guidebook, this training is expected to have a long-term impact on educational development in the West Lombok area, preparing students to face future challenges with the necessary 21st century skills.